Evolution in the treatment of gastroenteropancreatic-neuroendocrine neoplasms, focus on systemic therapeutic options: a systematic review. (July 2015) - Pusceddu, Sara; De Braud, Filippo; Festinese, Fabrizio; Bregant, Cristina; Lorenzoni, Alice; Maccauro, Marco; Milione, Massimo; Concas, Laura; Formisano, Barbara; Leuzzi, Livia; Mazzaferro, Vincenzo; Buzzoni, Roberto
ABSTRACT : Neuroendocrine neoplasms (NENs) are a group of heterogeneous tumors. The present review discusses current therapeutic strategies for the treatment of gastro-entero-pancreatic NEN. Several systemic options are currently available, including medical systemic chemotherapy, biological drugs, somatostatin analogs and peptide receptor radionuclide therapy. The carcinoid syndrome can be adequately controlled with somatostatin analogs; chemotherapy has shown positive outcomes in poor prognosis patients, and peptide receptor radionuclide therapy is a promising treatment based on the use of radioisotopes for advanced disease expressing somatostatin receptors. Targeted therapies, such as multikinase inhibitors and monoclonal antibodies are also recommended or under evaluation for the treatment of advanced NENs, but some critical issues in clinical practice remain unresolved. Depending upon the development of the disease, a multimodal approach is recommended. The treatment strategy for metastatic patients should be planned by a multidisciplinary team in order to define the optimal sequence of treatments.